Pervasive selection for and against antibiotic resistance in inhomogeneous multistress environments - Remy Chait (Nature Portfolio, 2016)
Antibiotic concentrations are low in most natural environments, except around localized antibiotic sources. Here, Chait et al.show that sub-inhibitory antibiotic levels can interact with many other stresses to generate complex patterns of selection for and against resistance to the antibiotic.